Aluminum Stress of Oriental Melon (Cucumis melo L.) Is Linked to the Dehydrin CmDHN3 - Chong Zhang; Qiang Chen; Xinqi Guo; Hongbo Pang; Ying Zhang (Horticulturae)
Dehydrins (DHNs; late embryogenesis-abundant D11 family) are a class of hydrophilic proteins involved in plant abiotic stress response. However, there is less information regarding DHN gene function in cucurbit crops. Herein, 34 DHN gene family members were identified and characterized in Cucumis sativus, Cucumis melo, Citrullus lanatus, Benincasa hispida, Lagenaria siceraria, and Cucurbita maxima. The DHN genes in the six cucurbit crops exhibited greater collinearity within subfamilies than between different subfamilies. Responses to stress (including low-temperature, salt, cadmium, and aluminum stress) varied among the DHN members, with a significant alteration in the expression of the acidic SnKn-type DHN gene CmDHN3 in response to aluminum stress. Subcellular localization analysis confirmed that CmDHN3 is expressed in the nucleus and cytoplasm. Virus-induced gene silencing (VIGS) revealed a remarkable decrease in CmDHN3 expression, which markedly increased malondialdehyde content, relative conductivity, and proline content in the roots and leaves of plants under aluminum stress. Transcriptome analysis showed that the decreased CmDHN3 expression reduced the expression of water channel protein-encoding genes. Interactions between CmDHN3 and CmAQP1 (MELO3C007188) and between CmDHN3 and CmAQP2 (MELO3C020774) were confirmed using yeast two-hybrid assays. These results clarify the pathway by which dehydrin genes are involved in the transcriptional-level response of melon to aluminum stress and provide a theoretical basis to comprehensively analyze the functions of this gene family in cucurbit crops.